Pengembangan Media Fun Flipbook Activity Dalam Meningkatkan Kemampuan Numerasi Kelas IV Di Sekolah Dasar - Wardhani, Intan Susetyo Kusumo (JURNAL PENDIDIKAN DASAR NUSANTARA, 2024)
The purpose of this study was to determine the validity of the development of fun flipbook activity media in improving the numeracy skills of fourth grade students, to determine the implementation of fun flipbook activity media in improving the numeracy skills of fourth grade students, and to test the effectiveness of fun flipbook activity media in improving the numeracy skills of fourth grade students. The method and type of research used in this study were RnD with the ADDIE development model. The instruments used in this study included questionnaires, observation sheets and tests. This study was conducted at SDN 2 Kendalrejo with research subjects of 38 fourth grade students with low, medium and high abilities. From the study it was known (1) the level of validity of fun flipbook activity, from expert validation showed a percentage achievement of 91.5% with a high category or with very valid criteria and feasible to use, (2) the level of implementation based on the observation sheet, implemented reached a percentage of 95.5% with a very high category (3) the level of effectiveness of fun flipbook activity reached a percentage of 94.72% with a high category and feasible to use. Based on the data above, it shows that the fun flipbook activity developed is stated to be very valid, has high implementation and is effective for use in learning. Based on the data above, it shows that the fun flipbook activity media developed is stated to be very valid, has high implementation and is effective for use in learning.